PENGARUH PENGETAHUAN PAJAK DAN PEMAHAAMAN PENERIMAAN DARI PAJAK BUMI DAN BANGUNAN TERHADAP KEPATUHAN WAJIB PAJAK - Widayanti, Raharjeng; Pratiwi, Yanna Eka; Lastianti, Siwidyah Desi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
Taxpayer compliance in paying PBB is determined by many factors. For example knowledge about taxes, ease of paying taxes, socialization of tax payments, and many more. This study aims to determine the effect of tax knowledge and understanding of revenue from land and building taxes on taxpayer compliance. The population in this study were all registered taxpayers in Kedamean District, Gresik Regency, East Java Province, totaling 46,807 taxpayers with a sample size of 348 respondents determined using the Issac table method. The instrument used to collect data was a questionnaire and analyzed with simple linear regression and multiple linear regression. The results of the study concluded that the taxpayer's knowledge of taxes and understanding of revenue from land and building tax independently had a positive effect on taxpayer compliance, as well as together.